2007
DOI: 10.1038/nature06350
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution with viruses drives the evolution of bacterial mutation rates

Abstract: Bacteria with greatly elevated mutation rates (mutators) are frequently found in natural and laboratory populations, and are often associated with clinical infections. Although mutators may increase adaptability to novel environmental conditions, they are also prone to the accumulation of deleterious mutations. The long-term maintenance of high bacterial mutation rates is therefore likely to be driven by rapidly changing selection pressures, in addition to the possible slow transition rate by point mutation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
275
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(290 citation statements)
references
References 29 publications
10
275
2
3
Order By: Relevance
“…Bacteria with a high mutation rate are frequently isolated in clinical settings [12,13] and in laboratory evolution experiments [14,15]. Their emergence is an eventual consequence of the genetic structure of asexuals, which allows mutator alleles to hitchhike with beneficial mutations occurring in the same genome [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria with a high mutation rate are frequently isolated in clinical settings [12,13] and in laboratory evolution experiments [14,15]. Their emergence is an eventual consequence of the genetic structure of asexuals, which allows mutator alleles to hitchhike with beneficial mutations occurring in the same genome [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…One of these was in the mutS gene, which is part of the DNA mismatch repair machinery. Mutations in this gene are known to lead to a high frequency of mutations in other bacteria (56)(57)(58). This mutator strain lost both of the mutations found in the initial resistant strain yet maintained resistance to all five phages, presumably due to the other mutations acquired, and even though only the phage used for initial isolation was present in the culture.…”
Section: Resultsmentioning
confidence: 99%
“…Second, different antibiotic resistance mechanisms could explain different degrees of pleiotropic growth costs; decreased cell permeability is often connected to clearly reduced growth in the absence of antibiotics [44]. Third, it has also been shown that bacterial hypermutator phenotypes bear small pleiotropic costs [45] and that hypermutators can be favoured under phage selection [46]. While further experiments are needed to test these hypotheses, we conclude that the cost of adaptation might not always limit fitness increases to multiple stresses as observed in this study.…”
Section: Discussionmentioning
confidence: 99%